Relationship Between Prenatal Class and Anxiety Levels oPregnant Women Facing Normal Delivery at Kartasura Community Health Center - Mona Isabella; Sulastri Sulastri (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Fear during pregnancy often arises related to miscarriage, fetal abnormalities and normal delivery. This anxiety increases as labor approaches. Health care providers need to provide comprehensive psychological care and support, such as through prenatal classes that increase the knowledge of pregnant women. This study aims to determine the relationship between prenatal classes and anxiety levels in pregnant women who will face normal delivery at the Kartasura Health Center. This study is a quantitative analytical study with a cross-sectional research design. The study will be conducted at the Kartasura Health Center and can be implemented in May 2024. The population in this study were 258 pregnant women who visited the Kartasura Health Center. The sampling technique was purposive sampling so that a research sample of 72 people was obtained. Data collection with a questionnaire in the form of interviews. Data analysis used Univariate and Bivariate analysis with the Chi-Square test. The results showed that there was a significant relationship between prenatal classes and the level of anxiety of pregnant women facing normal delivery at the Kartasura Health Center (p-value = 0.028). The implementation of prenatal classes can be given more attention. Health workers try to increase awareness of pregnant women about the importance of attending prenatal classes to improve knowledge and health, both physically and mentally, of pregnant women. Keywords: Prenatal class, Anxiety, Normal labor